Unfiltered : conflicts over tobacco policy and public health - Feldman, Eric A.; Bayer, Ronald (Cambridge, Mass. : Harvard University Press, 2004)
"Unfiltered tells the story of how anti-smoking advocates, public health professionals, bureaucrats, and tobacco corporations have clashed over smoking regulation. The nations discussed in this book - Australia, Canada, Denmark, France, Germany, Japan, the United Kingdom, and the United States - restrict tobacco advertising, tax tobacco products, and limit where smoking is permitted. Each is also struggling to shape a tobacco policy that ensures corporate accountability, protects individual liberty, and asserts the state's public health power."--Jacket.
Children and bystanders first: the ethics and politics of tobacco control in the United States / Ronald Bayer and James Colgrove -- The limits of tolerance: cigarettes, politics, and society in Japan / Eric A. Feldman -- Rights and public health in the balance: tobacco control in Canada / Christopher P. Manfredi and Antonia Maioni -- The politics of tobacco control in Australia: international template? / John Ballard -- Militants, manufacturers, and governments: postwar smoking policy in the United Kingdom / Virginia Berridge -- Liberté, Egalité, Fumée: smoking and tobacco control in France / Constance A. Nathanson -- Between paternalism and voluntarism: tobacco consumption and tobacco control in Germany / Günter Frankenberg -- Holy smoke, no more? Tobacco control in Denmark / Erik Albæk -- Tobacco-control policy in the European Union / Anna Gilmore and Martin McKee -- Difference and diffusion: cross-cultural perspectives on the rise on anti-tobacco policies / Allan M. Brandt -- Tobacco control in comparative perspective: eight nations in search of an explanation / Theodore R. Marmor and Evan S. Lieberman -- Conclusion: Lessons from the comparative study of tobacco control.
Includes bibliographical references (pages 309-385) and index.
JSTOR
Keywords: European Union; Tobacco industry -- Government policy; Tobacco use -- Health aspects -- Government policy; Advertising -- Tobacco -- Government policy; Tobacco -- Taxation; Cross-cultural studies; Medical policy; Smoking Prevention; Cross-Cultural Comparison; Health Policy; Tobacco Use Disorder -- prevention & control; Tabac -- Industrie -- Politique gouvernementale; Tabagisme -- Aspect sanitaire -- Politique gouvernementale; Tabac -- Publicité -- Politique gouvernementale; Tabac -- Impôts.; Études transculturelles; Politique sanitaire; LAW / Health; Medical policy; Cross-cultural studies; Tobacco industry -- Government policy; Tobacco -- Taxation; Rauchen; Gesundheitspolitik; Politische Kontrolle; Industriestaaten; Roken; Volksgezondheid; Overheidsbeleid; Wetgeving; Tabaksindustrie; Tobacco habit -- Health aspects -- Government policy; Book